2015
DOI: 10.1152/ajpregu.00286.2015
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care cardiac troponin test accurately predicts heat stroke severity in rats

Abstract: Audet GN, Quinn CM, Leon LR. Point-of-care cardiac troponin test accurately predicts heat stroke severity in rats. Am J Physiol Regul Integr Comp Physiol 309: R1264 -R1272, 2015. First published August 19, 2015; doi:10.1152/ajpregu.00286.2015.-Heat stroke (HS) remains a significant public health concern. Despite the substantial threat posed by HS, there is still no field or clinical test of HS severity. We suggested previously that circulating cardiac troponin (cTnI) could serve as a robust biomarker of HS se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Emerging evidence supports the value of Ang II and Ang-(1-7) as potential biomarkers, mainly in inflammatory diseases [19, 20]. In addition, considering that liver damage is always delayed by a few days, there are few reliable markers to predict the occurrence and prognosis of liver damage as a result of heatstroke [21, 22]. In this study, we first found that the reversed ratio of Ang II and Ang-(1-7) was associated with hepatic damage and illness severity in heatstroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence supports the value of Ang II and Ang-(1-7) as potential biomarkers, mainly in inflammatory diseases [19, 20]. In addition, considering that liver damage is always delayed by a few days, there are few reliable markers to predict the occurrence and prognosis of liver damage as a result of heatstroke [21, 22]. In this study, we first found that the reversed ratio of Ang II and Ang-(1-7) was associated with hepatic damage and illness severity in heatstroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several extra-cardiac mechanisms were proposed as contributing processes to myocardial damage and development of cardiac arrhythmias in heatstroke, in both humans and animals, including myocardial hypoperfusion and injury, lactic acidosis, hypoxemia, electrolyte imbalance and possibly, direct thermal injury. [87][88][89] Serum cardiac troponins I and T concentrations are increased in naturally occurring exertional and environmental heatstroke in both human patients and dogs, as well as in rats induced with heatstroke. 63,87,90,91 In the latter, cardiac troponin concentration accurately predicted the severity of the heatstroke.…”
Section: Myocardial Damage and Cardiac Arrhythmiamentioning
confidence: 99%
“…[87][88][89] Serum cardiac troponins I and T concentrations are increased in naturally occurring exertional and environmental heatstroke in both human patients and dogs, as well as in rats induced with heatstroke. 63,87,90,91 In the latter, cardiac troponin concentration accurately predicted the severity of the heatstroke. 87 Necropsy findings in dogs with fatal naturally occurring heatstroke invariably showed mild to severe subendocardial, myocardial and epicardial hemorrhages and hyperemia, 58 suggesting that DIC has a pivotal role in the pathogenesis of heatstrokeassociated cardiac arrhythmias.…”
Section: Myocardial Damage and Cardiac Arrhythmiamentioning
confidence: 99%
“…While we did not measure responses at hypothermic depth in the SEV rats, our data at 1D and T c,Max in conjunction with previous mouse studies suggest that increased hypothalamic chemokine/cytokine expression is linked to the recovery T c profile, and could be driving hypothermia in a yet undetermined manor. The key point separating our two rodent models is that hypothermia during recovery in mice is considered a regulated response and necessary for recovery [7,34,39], while it is a marker of severity in rats [6,40]. However, we have previously shown in our mouse model that the greatest alterations in gene expression of the brain (and systemically) occur at hypothermia depth [12].…”
mentioning
confidence: 99%